IMPROVED PERFORMANCE OF BUSINESS OWNERS WITH SOCIAL CAPITAL, HUMAN CAPITAL, AND ENTREPRENEURIAL COMPETENCE - Triono, Tomi Agus; Kirana, Kusuma Chandra; Fadhilah, Muinah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
MSMEs are one of the important parts of the country's economic growth, so it must be supported by competent human resources. The purpose of this study was to find out how much the level of performance of business owners is influenced by social capital, human capital, and entrepreneurial competence. The method used was a quantitative approach with questionnaires for data retrieval, and it was tested using SmartPLS 3.3 software. The results of this study showed that social capital has an effect on entrepreneurial competence, social capital has no effect on performance, human capital affects entrepreneurial competence, human capital affects performance, and entrepreneurial competence affects performance. Entrepreneurial competence as a mediation variable is able to increase the influence of social capital and human capital on performance. There needs to be more effort by the regional government of Yogyakarta to increase the social capital of business owners so that they can achieve common goals and optimal performance.